2022
DOI: 10.1038/s41467-022-29617-6
|View full text |Cite
|
Sign up to set email alerts
|

A Maluku Sea intermediate western boundary current connecting Pacific Ocean circulation to the Indonesian Throughflow

Abstract: The Indonesian Throughflow plays an important role in the global ocean circulation and climate. Existing studies of the Indonesian Throughflow have focused on the Makassar Strait and the exit straits, where the upper thermocline currents carry North Pacific waters to the Indian Ocean. Here we show, using mooring observations, that a previous unknown intermediate western boundary current (with the core at ~1000 m depth) exists in the Maluku Sea, which transports intermediate waters (primarily the Antarctic Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…(2009), and other locations along the eastern ITF route. An intermediate western boundary current (WBC) with the core at 1,000 m depth carrying the AAIW was observed in the Maluku Channel (Yuan et al., 2022). The estimated transport of this WBC is −2.28 Sv (shown as −2.3 in Figure 2) over the depth range of 450–1,800 m. It was suggested that part of this WBC (−1.36 Sv) flows southward through the Lifamatola Passage and the rest recirculates back in the central and eastern sectors of the channel.…”
Section: Model Evaluationmentioning
confidence: 99%
“…(2009), and other locations along the eastern ITF route. An intermediate western boundary current (WBC) with the core at 1,000 m depth carrying the AAIW was observed in the Maluku Channel (Yuan et al., 2022). The estimated transport of this WBC is −2.28 Sv (shown as −2.3 in Figure 2) over the depth range of 450–1,800 m. It was suggested that part of this WBC (−1.36 Sv) flows southward through the Lifamatola Passage and the rest recirculates back in the central and eastern sectors of the channel.…”
Section: Model Evaluationmentioning
confidence: 99%
“…They flow through Lifamatola Strait, where transport volume is estimated at 2.4-2.5 Sv, mainly near the bottom (van Aken et al, 2009). A recent study found that the Maluku Sea transports Antarctic Intermediate Water (AAIW) into Lifamatola Passage above the bottom overflow (Yuan et al, 2022). Secondary ITF portals provide a source of fresh water, which influences stratification in the ITF (South China Sea Throughflow, Figure 1a) (Gordon et al, 2012;Wang et al, 2006;Zeng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This region is unique due to its complex topography, land-marine biodiversity, distinct upper ocean circulation, and atmospheric processes over the IMC that potentially influence climate processes on a global scale (Lee et al 2019;Yoneyama and Zhang 2020). Ocean circulation in the Banda Sea is part of the branch of the Indonesian Throughflow (ITF), an intrinsic part of the global ocean circulation that transports heat from the Pacific Ocean into the south-eastern tropical Indian Ocean (Yuan et al 2018(Yuan et al , 2022. The ITF exerts its influence primarily on the interior circulation of the western and southern boundaries of the Banda Sea (Zhu et al 2019).…”
Section: Introductionmentioning
confidence: 99%